(untitled) (Medical Forum Monthly, 2023)
Objective: To evaluate the biochemical and hematological alterations in patients having Dengue without Warning Signs (DWWS) for predicting the severity of disease Study Design: Observational Case Control study Place and Duration of Study: This study was conducted at the Clinical Pathology Department of Jinnah Post Graduate Medical Center (JPMC), Karachi, from November 2022 to February 2023. Materials and Methods: The study encompassed 200 participants, presented at the medical and surgical OPDs, suspected for DWWS. These fulfilled the inclusion criteria (acute febrile illness, generalized rash on the body, vomiting, retro-orbital pain, and arthralgia/myalgia. Febrile illness regarded as body temperature above 38.40 Fahrenheit). On the basis of positive NS 1 or IgM or both patients were assigned to DWWS group (100 individuals) where as those with negative test results, to the control group. Blood samples were collected, from both groups, for the assessment of hematological and biochemical parameters. The data organization and analysis was performed using SPSS software version 20. Results: Out of the 200 participants with febrile presentation, those positive for DENV exhibited an elevated mean hematocrit (49.06±3.89) and a low platelet count (73.64 ±28.86). Biochemical alterations in the DWWS group included significantly elevated levels of mean GGT (49. ± 49.42 ), Serum ferritin (251.79 ±472.79) , hsCRP (11.73±20.39) & serum triglycerides (230.60±275.51), where serum cholesterol (124.30±59.85), Vitamin D levels (14.241±7.11) were significantly low in this group compared to the controls. Conclusion: This study indicated the potential role of different biochemical and hematological parameters as Predictive markers for severity of dengue.